Determination of Lipoxygenase Activity in Cereals Grains Using a Silver Nanoparticles Assay - Raybel Muñoz; Jose A. Rodriguez; M. Elena Páez-Hernández; Irais Sánchez-Ortega; Eva M. Santos (Journal of Chemistry)
A spectrophotometric method based on the use of silver nanoparticles is presented for the determination of lipoxygenase activity in cereal grains. The method involves the synthesis of prism silver nanoparticles with a maximum absorption at 752 nm, followed by the abatement of the signal as a consequence of the oxidation produced by hydroperoxides generated in the enzymatic reaction. The quantification of the hydroperoxides produced by reaction of lipoxygenase with linoleic acid allows the determination of the enzyme activity in cereal grains. Under optimal conditions, the linear range of the calibration curve ranges from 1.0 to 5.0 μM, with a limit of detection of 0.34 μM. The method was validated comparing the results with those obtained by ferrous-xylenol orange method. A relative standard deviation < 5.0% was obtained in all cases and no significant differences were observed (p<0.05).